Генетска основа на Алцхајмеровата болест - Трајковски, Владимир (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2010)
Alzheimer's disease (AD) is an irreversible, progressive brain disease that slowly destroys memory and thinking skills, and eventually even the ability to carry out the simplest tasks. Neurodegeneration is estimated to start 20-30 years before clinical symptoms become apparent. The most common neuropathological feature of AD is the presence of neurofibrillary tangles and amyloid deposits that form plaques and cerebrovascular accumulations. AD is divided into familial and sporadic forms. AD is considered familial when more than one person in a family is affected, while sporadic refers to AD cases when no other cases have been seen in close family members. Almost all cases of sporadic AD are late-onset, while approximately 90% of familial AD is late-onset. Less than 10% of all AD cases are familial early-onset. Familial early-onset AD is inherited in an autosomal dominant manner, meaning that inheritance of one mutant allele of APP, PSEN1, or PSEN2 almost always results in development of the disease. The most well established genetic risk factor for development of sporadic late-onset AD is inheritance of the ε4 allele of the apolipoprotein E (APOE) gene. More than 300 genetic polymorphisms have been involved with AD, demonstrating that this condition is polygenic and with a complex pattern of inheritance. Effort has been made to seek therapies that could reduce Aβ products by influencing APP processing. The most hopeful advance in the research for treatment of AD is the discovery of chemical compounds that show promise in reducing amyloid formation or reducing tau phosphorylation. There is still a long way between the huge amount of data gathered so far and the actual application toward the full understanding of AD, but the final goal is to develop precise tools for diagnosis and prognosis, creating new strategies for better treatments based on genetic profile.
Gebetic basis of Alzheimer disease
Keywords: Алцхајмерова болест, генетика, гени, студии, АПОЕε4 алел